2016
DOI: 10.1007/s11255-015-1207-6
|View full text |Cite
|
Sign up to set email alerts
|

Is low magnesium a clue to arteriovenous fistula complications in hemodialysis?

Abstract: Hypomagnesemia is a significant pro-atherogenic factor and an important predictor of arteriovenous fistula complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Several studies have shown that a lack of magnesium causes vascular stenosis, platelet aggregation, inflammation, and oxidative stress, leading to dysfunction of the vascular endothelium and calcifications. The results of our earlier studies showed that magnesium may play an important role in the development or acceleration of atherosclerosis and, finally, in the development of vascular calcification in patients with complications of the AVF for HD . Rare investigations on circulating magnesium concentrations in dialysis patients found a clear association between low serum magnesium levels and the incidence of peripheral artery calcification .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Several studies have shown that a lack of magnesium causes vascular stenosis, platelet aggregation, inflammation, and oxidative stress, leading to dysfunction of the vascular endothelium and calcifications. The results of our earlier studies showed that magnesium may play an important role in the development or acceleration of atherosclerosis and, finally, in the development of vascular calcification in patients with complications of the AVF for HD . Rare investigations on circulating magnesium concentrations in dialysis patients found a clear association between low serum magnesium levels and the incidence of peripheral artery calcification .…”
Section: Discussionmentioning
confidence: 74%
“…However, the role of magnesium in this population is still insufficiently explained . Our recent research has found that the patients with complications of AVF has a significantly lower concentration of magnesium, which indicates the need for further research that could provide information about the actual impact of magnesium carbonate as a phosphate binder to prevent of thrombosis fistula. Results of this research are also indicate that magnesium is involved in the development of vascular calcification in patients with complications of the AVF, as the correlation and multiple regression analyses showed marked association between magnesium level and duration of the AVF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Immature PLT fraction is elevated in patients with type 2 diabetes and associated with poor glycaemic control (37) . The Mg level was inversely correlated with leucocyte (P = 0⋅028) and PLT (P = 0⋅016) counts on patients with haemodialysis (38) . However, serum Mg was inversely associated with thrombocytopenia in healthy adults (39) .…”
Section: Discussionmentioning
confidence: 96%